1984
DOI: 10.1007/bf00499285
|View full text |Cite
|
Sign up to set email alerts
|

Additional evidence implicating Triticum searsii as the B-genome donor to wheat

Abstract: In vitro DNA:DNA hybridizations and hydroxyapatite thermal-elution chromatography were employed to identify the diploid wheat species ancestral to the B genome of Triticum turgidum. 3H-T. turgidum DNA was hybridized to the unlabeled DNAs of T. urartu, T. speltoides, T. sharonensis, T. bicorne, T. longissimum, and T. searsii. 3H-Labeled DNAs of T. monococcum and a synthetic tetraploid AADD were hybridized with unlabeled DNAs of T. urartu and T. searsii to determine the relationship of the A genome of polyploid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…longissima (Tanaka, 1956; Konarev et al, 1976; Konarev, 1980; Peacock et al, 1981), Ae. searsii (Feldman and Kislev, 1977; Nath et al, 1983, 1984; Kerby et al, 1990; Liu et al, 2003), Ae. sharonensis (Kushnir and Halloran, 1981) or yet unknown species of the Emarginata group (Kerby et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…longissima (Tanaka, 1956; Konarev et al, 1976; Konarev, 1980; Peacock et al, 1981), Ae. searsii (Feldman and Kislev, 1977; Nath et al, 1983, 1984; Kerby et al, 1990; Liu et al, 2003), Ae. sharonensis (Kushnir and Halloran, 1981) or yet unknown species of the Emarginata group (Kerby et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…However, poor meiotic pairing between T. speltoides chromosomes and those of hexaploid wheat cast doubt on this hypothesis (Kimber and Athwal, 1972). Subsequently, several other species in section Sitopsis, including T. longissimum (Feldman, 1979), T. searsii (Nath et al, 1983(Nath et al, , 1984, T. bicorne (Sears, 1956), and T. sharonense (Kushnir and Halloran, 1981), have been proposed as donors of the B genome to polyploid wheat. Kerby and Kuspira (1987) have reviewed the often contradictory evidence providing support for each of the Sitopsis species as donors of the B genome.…”
mentioning
confidence: 99%
“…Studies that are more recent have reported Ae. searsii (termed T. searsii) as the B-genome donor (Nath et al 1983(Nath et al , 1984. Feldman and Levy (2005) provided some explanations on the ambiguous nature of the B-genome, which include: (1) the diploid donor of the B-genome being extant but not yet discovered; (2) the diploid donor of the B-genome undergoing massive genomic changes after the formation of the allotetraploid; and…”
Section: Discussionmentioning
confidence: 99%